Dietary Diversity and Associated Factors Among Adult HIV Positive Patients on Anti-Retroviral Therapy in Public Hospitals of Kembata Tembaro Zone, Southern Ethiopia - Markos M (Dove Medical Press, 2020)
Melese Markos,1 Tsegaye Lolaso,2 Abrham Mengistu,3 Zerihun Tariku1 1Department of Public Health, College of Medicine and Health Science, Dire Dawa University, Dire Dawa, Ethiopia; 2School of Public Health, College of Health and Medicine Science, Wolaita Sodo University, Wolaita Sodo, Ethiopia; 3Department of Public Health, College of Health and Medicine Science, Wachamo University, Hossaina, EthiopiaCorrespondence: Melese Markos Tel +251-916-138-371Email melesemarkos@gmail.comBackground: Nutrition is a significant factor in all stages of HIV. Dietary management of HIV-positive patients is key to supporting their capacity to continue participating in the workforce and contributing to socio-economic growth. Few studies have been conducted regarding this important public health problem of dietary diversity throughout the developing countries including Ethiopia. Therefore, this study assesses the magnitude and factors associated with dietary diversity among HIV-positive patients attending antiretroviral therapy (ART) clinics at Public Hospitals in Kembata Tembaro Zoni, Southern Ethiopia.Methods and Materials: An institutional-based cross-sectional study was conducted from January 01/2019 to 30/2019 on 341 adult HIV-positive patients on ART at two randomly selected public hospitals in the study area. A systematic random sampling technique was applied to select study subjects from each facility proportionally. Bivariable and multivariable logistic regression analyses were done to identify factors associated with individual dietary diversity. Logistic regression analysis with 95% confidence interval (CI) was estimated to measure the strength of association. Level of significance for statistical tests was set at p < 0.05.Results: This study shows 60.1% (95% CI: 55– 65) of patients had inadequate dietary diversity. Average monthly income of less than 1000 Ethiopian Birr (AOR: 1.82, 95% CI: 1.04– 3.17), being female (AOR = 2.99, 95% CI: 1.67– 5.37), duration of ART less than 1 year (AOR = 3.77, 95% CI: 1.42– 10.02) and lack of dietary counseling (AOR =0.54, 95% CI: 0.30– 0.97) were factors associated with low dietary diversity.Conclusion: Low dietary diversity was a major nutritional problem in HIV-positive patients. Low average monthly income, being female, duration of participants on ART, and lack of dietary counseling were the factors associated with low dietary diversity. To alleviate these problems, exceptional attention in nutritional care should be given to HIV-positive patients and they require appropriate counseling and support during early initiation of ART.Keywords: dietary diversity, HIV positives, patients, southern, Ethiopia